J Curve in Patients Randomly Assigned to Different Systolic Blood Pressure Targets: An Experimental Approach to an Observational Paradigm. Issue 23 (5th December 2017) - Kalkman, Deborah N.; Brouwer, Tom F.; Vehmeijer, Jim T.; Berger, Wouter R.; Knops, Reinoud E.; de Winter, Robbert J.; Peters, Ron J.; van den Born, Bert-Jan H.
Abstract : Background: Low systolic blood pressure (SBP) values are associated with an increased risk of cardiovascular events, giving rise to the so-called J-curve phenomenon. We assessed the association between on-treatment SBP levels, cardiovascular events, and all-cause mortality in patients randomized to different SBP targets. Methods: Data from 2 large randomized trials that randomly allocated hypertensive patients at high risk for cardiovascular disease to intensive (SBP<120 mm Hg) or conventional (SBP<140 mm Hg) treatment were pooled and harmonized for outcomes and follow-up duration. Using natural cubic splines, we plotted the hazard ratio for all-cause mortality and cardiovascular events against the mean on-treatment SBP per treatment group. Results: The pooled data consisted of 194 875 on-treatment SBP measurements in 13 946 patients (98.9%). During a median follow-up of 3.3 years, cardiovascular events occurred in 1014 patients (7.3%), and 502 patients died (3.7%). For both blood pressure targets, an identical shape of the J curve was present, with a nadir for cardiovascular events and all-cause mortality just below the SBP target. Patients in the lowest SBP stratum were older, had a higher body mass index, smoked more often, and had a higher frequency of diabetes mellitus and cardiovascular events. Conclusions: Low on-treatment SBP levels are associated with increased cardiovascular events and all-cause mortality. This association is independent of the attained blood pressure level because the J curve aligns with the SBP target. Our results suggest that the benefit or risk associated with intensive blood pressure–lowering treatment can be established only via randomized clinical trials. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifiers: NCT01206062 and NCT00000620. Abstract : Supplemental Digital Content is available in the text.